The Role of School Principals in Managing Human Resources Management in Improving the Quality of Education in Gugus 6 State Elementary Schools, Kota Bahagia District, South Aceh - Dian Erlita; Rita Novita; Musdiani Musdiani (Dinasti Publisher, 2024)
This research aims to analyze the role of school principals in managing human resources towards improving the quality of education at the Gugus 6 State Elementary School, Kota Bahagia District, South Aceh. The approach used in this research is a qualitative approach with the type of research used in this research being a multisite study. In this research, three data collection techniques were used, namely observation, interviews, documentation. Qualitative data analysis techniques in this research were carried out interactively through the process of data reduction, data display, and drawing conclusions/verification. The results of the analysis prove that the role of the principal in managing Human Resources at Gugus 6 State Elementary School, Kota Bahagia District, South Aceh is by carrying out good human resource planning, attracting human resources (recruitment) for applicants who pass the requirements, selection and placement. in accordance with their profession, holding training to improve the abilities of teachers and administrative staff, holding work performance assessments of teachers and employees every week, month or year to improve the performance of teachers and employees, and providing welfare to teachers and administrative staff in the form of monthly salaries and allowances.